C18-diterpenoid alkaloids in tribe Delphineae (Ranunculaceae): phytochemistry, chemotaxonomy, and bioactivities. Issue 1 (22nd December 2021) - Yan, Yuanfeng; Li, Xing; Wang, Ze; Yang, Xiaoyan; Yin, Tianpeng
Abstract : This review systematically summarizes the C18 -diterpenoid alkaloid (DA) compositions isolated from the genera Aconitum and Delphinium in the Delphineae tribe (Ranunculaceae). Abstract : This review systematically summarizes the C18 -diterpenoid alkaloid (DA) compositions isolated from the genera Aconitum and Delphinium in the Delphineae tribe (Ranunculaceae). A total of 117 distinct C18 -DA components have been reported, including 58 lappaconitine-type DAs, 54 ranaconitine-type DAs, and five rearranged-type DAs. These components mainly originated from plants from the subgenus Lycoctonum in the genus Aconitum or less frequently from plants within the genus Delphinium . Natural C18 -DAs have exhibited a wide range of bioactivities, including analgesic, antiarrhythmic, anti-inflammatory, anti-tumor, and insecticidal activities, which are closely related to their chemical structures. The high chemical and biological diversities among the reported C18 -DA constituents in Delphineae plants indicated their potential as a vast resource for drug discovery. Additionally, the Delphineae plant C18 -DAs exhibited chemotaxonomic values and showed a high regularity of distribution at different taxonomic levels; therefore, the Delphineae plant C18 -DAs can serve as good chemical molecular markers in the taxonomic treatment of plants within this tribe, especially in the infrageneric division.